2013
DOI: 10.1021/jp400051b
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Noncovalent Interactions in Catenane Supramolecular Complexes: Calibrating the MM3 Force Field with ab Initio, DFT, and SAPT Methods

Abstract: The design and assembly of mechanically interlocked molecules, such as catenanes and rotaxanes, are dictated by various types of noncovalent interactions. In particular, [C-H⋯O] hydrogen-bonding and π-π stacking interactions in these supramolecular complexes have been identified as important noncovalent interactions. With this in mind, we examined the [3] catenane 2·4PF6 using molecular mechanics (MM3), ab initio methods (HF, MP2), several versions of density functional theory (DFT) (B3LYP, M0X), and the dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…As far as cluster models of the liquid phase are concerned, SAPT has been applied to elucidate the origins of interactions involving ionic liquids 50,[239][240][241][242] and to understand the π − π stacking occurring in an organic solvent. 243 Besides the endohedral fullerenes mentioned earlier, the SAPT and SAPT(DFT) energy decompositions have been applied to other supramolecular complexes including catenanes, 244 porphyrins and metalloporphyrins, 245 and the cucurbit [7]uril macrocycle. 246 SAPT0 has been used to decompose interaction energies of dimers relevant to organic electronics 247 ; in particular, it has been proposed to improve electronic couplings via an enhancement of charge penetration brought about by incorporating large heteroatoms in π-conjugated cores.…”
Section: 122mentioning
confidence: 99%
“…As far as cluster models of the liquid phase are concerned, SAPT has been applied to elucidate the origins of interactions involving ionic liquids 50,[239][240][241][242] and to understand the π − π stacking occurring in an organic solvent. 243 Besides the endohedral fullerenes mentioned earlier, the SAPT and SAPT(DFT) energy decompositions have been applied to other supramolecular complexes including catenanes, 244 porphyrins and metalloporphyrins, 245 and the cucurbit [7]uril macrocycle. 246 SAPT0 has been used to decompose interaction energies of dimers relevant to organic electronics 247 ; in particular, it has been proposed to improve electronic couplings via an enhancement of charge penetration brought about by incorporating large heteroatoms in π-conjugated cores.…”
Section: 122mentioning
confidence: 99%
“…35 The conformational freedom of the methoxy and methyl substituents was thoroughly analysed by running calculations using ɷB97X-D/6-31G(d). After this analysis, the most stable structures were used for further geometry optimizations and frequency calculations using the 37,38 We used the functionals ɷB97X-D, 33 B3LYP, [39][40][41] B3LYP-D3, [39][40][41][42] B3LYP-D3BJ [39][40][41][42] and M06-L 43 in this study. Previous studies of host-guest complexes have indicated that SCS-MP2 better predicts the change in energies of complexes with weak non-covalent interactions 38,44,45 compared to other commonly used DFT functionals.…”
Section: Computational Detailsmentioning
confidence: 99%
“…where the total energy of the molecular switch system is described by E complex and E thread and E macrocycle refers to the energy of the isolated monomers . The E b values imply binding interactions between different recognition sites and the macrocycle.…”
Section: Resultsmentioning
confidence: 99%